Spatial structure of in situ reflectance in coastal and inland waters: implications for satellite validation - Jordan, Thomas M.; Simis, Stefan G. H.; Selmes, Nick; Sent, Giulia; Ienna, Federico; Martinez-Vicente, Victor (Frontiers in Remote Sensing, 2023)
Validation of satellite-derived aquatic reflectance involves relating meter-scale in situ observations to satellite pixels with typical spatial resolution ∼ 10-100 m within a temporal 'matchup window' of an overpass. Due to sub-pixel variation these discrepancies in measurement scale are a source of uncertainty in the validation result. Additionally, validation protocols and statistics do not normally account for spatial autocorrelation when pairing in situ data from moving platforms with satellite pixels. Here, using high-frequency autonomous mobile radiometers deployed on ships, we characterize the spatial structure of in situ Rrs in inland and coastal waters (Lake Balaton, Western English Channel, Tagus Estuary). Using variogram analysis, we partition Rrs variability into spatial and intrinsic (non-spatial) components. We then demonstrate the capacity of mobile radiometers to spatially sample in situ Rrs within a temporal window broadly representative of satellite validation and provide spatial statistics to aid satellite validation practice. At a length scale typical of a medium resolution sensor (300 m) between 5-35 % (median values across spectral bands and deployments) of the variation in in situ Rrs was due to spatial separation. This result illustrates the extent to which mobile radiometers can reduce validation uncertainty due to spatial discrepancy via sub-pixel sampling. The length-scale at which in situ Rrs became spatially decorrelated ranged from ∼ 100-1000 m. This information serves as a guideline for selection of spatially independent in situ Rrs when matching with a satellite image, emphasizing the need for either downsampling or using modified statistics when selecting data to validate high resolution sensors (sub 100 m pixel size).